Epidermal Cyst on the Scalp Induced by Forceps Injury During Delivery: A Case Report and Epidemiological Analysis of 3949 Patients - Liu M; Liu X; Wang Y; Wang Z; Tuo H; Feng Y; Zheng Y (Dove Medical Press, 2023)
Meng Liu,1,* Xinyi Liu,1,* Yuqian Wang,1 Ziyang Wang,1 Huihui Tuo,1 Yiguo Feng,2 Yan Zheng1 1Department of Dermatology, the First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, People's Republic of China; 2Department of Dermatology, the Second Affiliated Hospital of Xi'an Jiaotong University, Xi'an, People's Republic of China*These authors contributed equally to this workCorrespondence: Yiguo Feng, The Second Affiliated Hospital of Xi'an Jiaotong University, Xi'an, People's Republic of China, Email fengyiguo70@163.com Yan Zheng, The First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, People's Republic of China, Email zenyan66@126.comBackground: Epidermal cysts are common benign epithelial tumors. They are known to result from penetrating-type injuries or infection of human papillomavirus. The differential diagnosis commonly includes multiplex steatocystoma, lipoma, and neurofibroma. Pathological examination is essential for diagnosis, and surgical excision is the recommended treatment.Objective: We report a case in a man who presented with a cystic lesion on the scalp over 22 years to provide clinical evidence for mechanism of epidermal cysts. We conducted epidemiological analysis of 3949 patients with epidermal cysts to clarify the epidemiological characteristics and clinical features of epidermal cysts.Patients and Methods: A total of 3949 individuals with confirmed epidermal cysts were collected for analysis. Data were expressed as mean ± SEM and analyzed using Student's t-test.Results: Our data showed that the mean age of diagnosis of males was statistically earlier than that of females (P< 0.001), but no significant difference in sex predilection was observed (P=0.55). The high incidence age of males and females was in the young and middle stage. Lesion locations were a bit different among age groups, but the face was the most common site of epidermal cyst at all age stages.Conclusion: Our case offers clinical evidence to the theory which refers trauma as one of the main causes of epidermal cysts in hair-bearing area. According to analysis of large number of samples, we can further support the idea that epidermal cyst has equal sex predilection and mainly occurs on the young and middle-aged adults. It is usually solitary and most likely to be found on face and trunk.Keywords: epidermal cysts, etiology, epidemiological analysis, treatment